2016
DOI: 10.1155/2016/7241591
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Minimal Residual Disease in the Myeloproliferative Neoplasms: Current Applications and Emerging Approaches

Abstract: The presence of acquired mutations within the JAK2, CALR, and MPL genes in the majority of patients with myeloproliferative neoplasms (MPN) affords the opportunity to utilise these mutations as markers of minimal residual disease (MRD). Reduction of the mutated allele burden has been reported in response to a number of therapeutic modalities including interferon, JAK inhibitors, and allogeneic stem cell transplantation; novel therapies in development will also require assessment of efficacy. Real-time quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The JAK2V617F mutation is usually detected by allele-specific PCR (Baxter et al, 2005;Scott et al, 2007;Scott, 2011;Tefferi et al, 2016a). Quantitative PCR methods such as RQ-PCR, ddPCR (droplet digital PCR), and NGS (Haslam and Langabeer, 2016;Link-Lenczowska et al, 2018;Arber et al, 2022). Peripheral blood counts, in patients with this mutation, show erythrocytosis, thrombocytosis, and/or leukocytosis.…”
Section: Jak2mentioning
confidence: 99%
“…The JAK2V617F mutation is usually detected by allele-specific PCR (Baxter et al, 2005;Scott et al, 2007;Scott, 2011;Tefferi et al, 2016a). Quantitative PCR methods such as RQ-PCR, ddPCR (droplet digital PCR), and NGS (Haslam and Langabeer, 2016;Link-Lenczowska et al, 2018;Arber et al, 2022). Peripheral blood counts, in patients with this mutation, show erythrocytosis, thrombocytosis, and/or leukocytosis.…”
Section: Jak2mentioning
confidence: 99%
“…Primary disease entities are polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). 183 At molecular level, mutations in JAK2 V617F are frequently observed, with ;95% of PV and 50% to 60% of ET/ PMF patients harboring this aberration. However, variants in other genetic regions are also common, including CALR exon 9 (;25% ET, ;35% PMF), MPL exon 10 (;4% PMF, ;1% ET), and JAK2 exon 12 (;4% PV).…”
Section: Chronic Myeloid Leukemiamentioning
confidence: 99%
“…[192][193][194] Some assays have already been used in clinical settings, demonstrating potential future utility for noninvasive disease monitoring. 183,[195][196][197][198] HTS-based approaches are not broadly established yet for routine MPN molecular diagnostics, but their capacity to simultaneously cover multiple genetic variants make them a promising tool for monitoring the genetic complexity of MPN. 184,185,197 Abdelhamid et al demonstrated in a proof-of-principle study robust detection of JAK2 V617F in PB by HTS with high concordance to qPCR, even at low AFs.…”
Section: Chronic Myeloid Leukemiamentioning
confidence: 99%
“…[ 26 ] Whether this phenomenon is also observed in patients with CALR + SVT remains to be answered. Given the number of methodological approaches available for the detection of CALR mutations,[ 27 , 28 ] careful validation and selection of a sensitive technique is required so as not to underdiagnose the potential underlying MPN. Secondly, all the pathologically annotated, MPN-associated CALR indel mutations result in a +1 alteration of the reading frame leading to a loss of the terminal calreticulin localization domain.…”
mentioning
confidence: 99%